Determination of Physicochemical Properties of Spent Engine Oil Polluted Soils Sites in Bali and its Environs, Taraba State, Nigeria (American Journal of Food Science and Technology, 2023)
The present study aimed to investigate the physicochemical properties of spent engine oil polluted soil sites in Bali and its Environs, Taraba State, Nigeria. The result revealed the particle size distribution show that polluted soils were categorized by relatively high sand content ranging from 30.2 – 80.2 %, and an average mean 58.08 %; silt 15.3-65.1 % (34.88 %) and clay 3.0-11.6 % (7.04 %). The textural descriptions of soils from the study sites were mostly sandy loam. The soil samples from Bali 1, Bali 2, Maihula, Garba Chede and Gazabu were of varying texture; sandy loam, loamy sand, sandy loam, silt loam and loamy respectively. The physicochemical properties of the soil samples show the temperature ranges from 31.33 - 31.58 0C with Garba Chede and Bali 2 having the lowest and highest respectively. The pH range between 5.6 - 6.2 with Bali 1 and Bali 2 having the lowest and highest respectively. The result shows that the soil samples are all slightly acidic. Samples from Bali 2 and Bali 1 were discovered to be the highest with 69.5% and least with 68.1% respectively for humidity. The electrical conductivity of the soil range is 1027.25 µs/cm and 474.0 µs/cm with Garba Chede and Gazabu having the highest and lowest respectively. The amount of total dissolved solid range is 14.5 – 30.0 mg/L making Gazabu have the highest lowest and Garba Chede the highest. Bali 1 and Bali 2 have the Cu range values of 3.500 and 1.080 ppm, showing the highest and lowest respectively. Pb and Cr were not detected in the samples.